2019
DOI: 10.1177/0284185119885119
|View full text |Cite
|
Sign up to set email alerts
|

CT angiogram findings in carotid-cavernous fistulas: stratification of imaging features to help radiologists avoid misdiagnosis

Abstract: Background Carotid-cavernous fistulas (CCFs) are commonly misdiagnosed on computed tomography angiography (CTA). Purpose This study sought to identify the most sensitive and specific imaging features of CCFs on CTA. Material and Methods A retrospective review identified 18 consecutive patients suspected of having a CCF on CTA and subsequently u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…High cavernous pressure might be the cause of these imaging findings. This is in line with the study by Benson et al, [6] which also identified CS asymmetry and or hyperdensity at the affected site in the majority of patients. "Enlarged" CS was less commonly acknowledged among falsepositive than true-positive cases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High cavernous pressure might be the cause of these imaging findings. This is in line with the study by Benson et al, [6] which also identified CS asymmetry and or hyperdensity at the affected site in the majority of patients. "Enlarged" CS was less commonly acknowledged among falsepositive than true-positive cases.…”
Section: Discussionsupporting
confidence: 91%
“…CCF often appears as an early enhancement of the CS on the side of the CCF, but not within the contralateral CS. Other imaging findings include dilatation of supraorbital vein, thickening of extraocular muscle, skull base fracture, and infarct [6].…”
Section: Discussionmentioning
confidence: 99%
“…With an incidence of only 0.2%, CCF are very rare vasculopathies after trauma [31]. Nevertheless, their typical findings, a dilatation of the superior ophthalmic vein, as well as proptosis, enlarged cavernous sinus and extraocular muscles, and orbital edema should initiate further invasive diagnostics through cerebral angiography [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…Even though MRI provides superior soft tissue contrast when compared to MSCT, and ultrasonography can survey the ocular globe precisely, MRI is less relevant in the acute setting due to long acquisition times as well as the possible risk of dislocation of metallic foreign bodies [10], and ultrasonography is contraindicated in cases of suspected globe rupture [11]. Nevertheless, contrast-enhanced MSCT can depict most soft tissue injuries accurately [12,13], and even hint to underlying carotid-cavernous fistulas (CCF) when dilated superior ophthalmic veins, exophthalmos, and orbital edema are present [14]. Furthermore, radiopaque intraorbital foreign bodies including glass fragments can be identified with a sensitivity of up to 90% on MSCT [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Classification is based on etiology (spontaneous or traumatic), hemodynamic characteristics (high-or low-flow), and anatomic characteristics (direct or indirect). [1][2][3] Direct CCFs are high-flow shunts with direct connections between the ICA and the cavernous sinus. 4 Common causes include blunt trauma, ruptured ICA aneurysm, Ehlers-Danlos Syndrome, and iatrogenic interventions.…”
Section: Introductionmentioning
confidence: 99%